Highway Safety Manual performance measures to hotspot identification: intersections at Porto city - Joana Martins (2013)
The Highway Safety Manual (HSM) provides guidance to safety professionals, however, due to the differences in crash data systems, local enforcement, driving behavior, and other factors leads to the need in assessing the international use of the HSM tools. The aim of the present study is to analyze and assess the application of the several performance measures proposed by the HSM under the network screening process. In order to do so, data from Porto city was used focusing in the case of the intersections, covering a four-year period. The analysis of the HSM performance measures leads to the conclusion that, in the national context, some of the measures are not possible to apply in a reliable manner due to the absence of, for example, specific accident costs, and others may need to be adapted to our context. Overall, from this initial application to the specific case of Porto intersections, some recommendations were pointed out as a future guidance for Portuguese context. However, future applications should be undertaken to confirm this first application results. In addition, from this work it was possible to point out improvements in terms of an adaptation of some of the HSM performance measures as well as the upgrade of data available and treatment.